Prototype and Application Implementation of Domestic and Foreign Labor Distribution - Amin, Muhammad; Muin , Agus Alim; Rasyidan , Muhammad; Wagino (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
In today's globalized world, many people are looking for domestic and international work for various reasons, such as higher salaries and better work experience. This application will assist job seekers in finding suitable job vacancies. With their skills and interests, as well as helping companies find candidates that suit their needs, information on job vacancies in the country and abroad. In the initial phase of developing this application, an application prototype will be created that includes the main features of this application. These features include information on job vacancies in the country and abroad, a job search system based on skills and interests, and a system design method using UML (Unified Modeling Language) design. This modeling is a system implementation of how to put a strategy into an image (visual) in the form of a diagram. This model facilitates the making of an application program or implementation and can be used in the long term, not only at this time but continuously and continuously. Because application programs are used for a long time, it is necessary to have a good and precise analysis of planning, design, and modeling, such as flow for application programs. In this study, using the UML method, submitting online job applications, as well as a notification.